(untitled) (JURNAL ULET (Utility, Earning and Tax), 2024)
The aim of this research is to analyze the financial performance of Kios Abil using financial ratio measures focusing on activity and profitability ratios. The method employed is descriptive with a quantitative approach, utilizing data collection techniques such as interviews and documentation. Data analysis entails examining the financial reports of Kios Abil for the years 2021 and 2022 through financial ratios. The findings indicate subpar performance in asset utilization, specifically in inventory turnover and asset turnover, for both years. However, regarding gross profit margin, the performance appears satisfactory, with a slight increase from 40% in 2021 to 42% in 2022. Conversely, net profit margin shows less satisfactory performance, improving marginally from 3% in 2021 to 4% in 2022. Furthermore, the return on assets reflects suboptimal performance, with respective net profit returns on assets of 1.5% in 2021 and 2.8% in 2022